THE INFLUENCE OF SELF-EFFICACY ON FUTURE ORIENTATION WITH SOCIAL SUPPORT AS A MEDIATION VARIABLE IN CHILDREN IN LPKA CLASS I TANGERANG - Wijata, I Kadek; Priyatmono, Budi (Journal of Management Small and Medium Enterprises (SMEs), 2025)
Limited space for movement and negative stigma as lawbreakers cause foster children to feel pessimistic and hopeless, thus reducing children's motivation to plan for their future. Various efforts are needed to build children to be optimistic about having a good future orientation. This study aims to provide an analysis of the relationship between self-efficacy and social support to the future orientation of fostered children while proving whether social support can be a mediator between self-efficacy and future orientation. This study uses quantitative research methods with non-probability sampling techniques on as many as 109 foster children. The data collection technique was carried out using a questionnaire. The measuring instruments used include General Self-Efficacy (GSE), Social Support Scale (SSS), and Future Orientation Scale (FOS). There are 77 statements that are used as indicators in this study. Data analysis techniques carried out through normality tests, multiple linear regression tests, correlation tests, Sobel tests, and determination tests were processed using JASP software version 0.14.1.0. The results showed a significant positive relationship between self-efficacy and future orientation with a coefficient of determination (R² = 0.318) as well as social support and future orientation with an R² of 0.473, and the Sobel test showed that social support significantly mediated the relationship between self-efficacy and future orientation. In conclusion, self-efficacy and social support contribute positively to the future orientation of foster children, and social support can act as a mediator to strengthen the influence of self-efficacy on future orientation. Keywords: Self-Efficacy; Future Orientation; Social Support; Foster Children; LPKA